2013
DOI: 10.1007/s00227-013-2188-6
|View full text |Cite
|
Sign up to set email alerts
|

Site fidelity and homing behaviour in intertidal fishes

Abstract: The theory of ecological cognition poses that the brains and behaviour of animals are shaped by the environmental challenges they face in their everyday lives. Site fidelity and homing ability was tested for five species of intertidal rock pool fish by tagging and displacing them to new rock pools at various distances from their 'home' rock pools. Three of the species were rock pool specialists whilst the remaining two spend a small proportion of their life in rock pools during early ontogeny. The three specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 36 publications
5
65
0
Order By: Relevance
“…Previous studies have also shown that site fidelity and homing behavior of fishes can vary with ontogeny (Yoshiyama et al 1992;Shima et al 2012;White and Brown 2013); older fish are more likely to risk the return to a home site across unfamiliar waters, although this is not always the case for all fishes (White and Brown 2013). Our homing results appear to be consistent with this view, but additional studies are needed to empirically test whether larger S. tubifer are actually more successful at homing than smaller fish.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have also shown that site fidelity and homing behavior of fishes can vary with ontogeny (Yoshiyama et al 1992;Shima et al 2012;White and Brown 2013); older fish are more likely to risk the return to a home site across unfamiliar waters, although this is not always the case for all fishes (White and Brown 2013). Our homing results appear to be consistent with this view, but additional studies are needed to empirically test whether larger S. tubifer are actually more successful at homing than smaller fish.…”
Section: Discussionsupporting
confidence: 90%
“…From short distances, S. tubifer likely uses visual cues to recognize and navigate within a familiar area to its daytime urchin host and probably has some spatial memory of a home site (e.g., White and Brown 2013), including the location of the host urchins in the area. However, to navigate back to a home site after displacement or to find a settlement site as a larva, S. tubifer presumably uses additional cues.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that if shrimp are displaced to unfamiliar territory, they either learn local features and remain in the new area or move to another low-tide refuge. A lack of evidence for homing in shrimps contrasts with reports that relocated rocky intertidal fish often return to original capture sites (White and Brown 2013;Thyssen et al 2014). This probably reflects expected differences in degrees of cognition between shrimp and fish.…”
Section: Discussionmentioning
confidence: 89%
“…In fishes, fidelity has been studied and indicated in a variety of intertidal environments (Gibson 1999), including shallow estuarine waterways (Weinstein and O'Neil 1986;Irlandi and Crawford 1997;Potthoff and Allen 2003), salt marshes (Lotrich 1975;Teo and Able 2003;Able et al 2006), and rocky intertidal pools (White and Brown 2013;Thyssen et al 2014). In crustaceans, few studies have attempted to address fidelity, but semiterrestrial crabs (Cannicci et al 1999;Forsee and Albrecht 2012) and large subtidal crabs (Stone and O'Clair 2002;Moore and Perrin 2007;Lebata et al 2012;Silva et al 2014) have shown tendencies to remain within small areas.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, marine fish have dispersive drifting planktonic larval stages and migrate at the adult stage for spawning. In contrast, the requirements of juvenile fishes differ from those of larvae, sub-adults, and adults (Adams et al, 2004) and, for many species, juveniles have relatively small home ranges (Peterson, 2003, White andBrown, 2013). Especially, for pleuronectiforms (Gibson, 2005), the influence of hydrodynamics and larval vertical movements may lead to important transport during the egg and larval stages (Savina et al, 2010).…”
Section: Introductionmentioning
confidence: 89%